Estimasi Kelajuan dan Volume Kendaraan Berdasarkan Model Makroskopik Arus Lalu Lintas Jalan Tol dengan Metode Extended Kalman Filter - Febriana Prihatiningsih; Sigit Pancahayani; Subchan Subchan (LPPM ITK, 2018)
In this thesis, the analysis of vehicles' determination of speed and volume in the traffic flow will be discussed by approach time. The analyzation of vehicles' speed and volume done by estimated on macroscopic term of traffic flow in the traffic jam with Extended Kalman Filter (EKF) method. The term of macroscopic views with measured the traffic variable by density the flow rate the flow rate of vehicle and also the vehicle speed's average. In the estimating process, forward difference scheme is implemented to the model and error are measured by Root Mean Square Error. The result showed that the estimation the average of the vehicle’s relative speed in a segment decreased when its volume of vehicle is increased and vice versa.